European Union’s Military Operations The Use of an Adaptive Approach to Face Security (Dis)Order (Decentering European studies: perspectives on Europe from its beyond, 2025)
To improve its capacity at managing crises, the European Union (EU) has sought to broaden its security and defense identity since the 1990s, deploying thirteen military operations and missions. Like other world powers, the EU has adapted its foreign policy to changing circumstances and strategic and economic interests. As the EU has enlarged and deepened its integration, questions arise about how its common foreign and security policies have evolved over time and whether these policies have expressed long-term interests or have constantly adapted to novel circumstances. This chapter discusses the reality of EU military engagement overseas through the lens of the complexity theory. The study confronts the aims presented in official EU narrative with practices on the ground through data collected in primary and secondary sources that highlight that the adaptive approach has led to three phases of modification in EU military operations and capabilities, as the EU attempts to become a global security provider: ambition during the first decade of the Common Security and Defense Policy, contraction between 2009 and 2016, and adjustment in today’s new global order. Conclusions suggest that not only is the EU’s institutional ambition of collective engagement in overseas operations in constant tension with the preferences and interests of its member states, but that EU operations are challenged by a changing global (dis)order necessitating constant adaptation.